CONTENT GAME, TOY AND PLAY IN TRAINING OF THE PHYSICAL EDUCATION TEACHER: REPORT OF AN EXPERIENCE (Fiep Bulletin - online, 2016)
This study aims to present the process of theming and questioning content "game, toy and game" in the training of physical education teachers and the search for decolonize the minds of academic training as a social representation of the use of such content on the court class, which has been taking place gradually in the course "Ethics, professional, human rights and citizenship" of the course of Physical Education of Amapá Higher Education Center - CEAP. To this end, we appropriate the theoretical and methodological procedures of qualitative research type experience report. As data collection technique we used the individual semi-structured interview. Found that the problem-solving educational process is a bridge to the awakening of a new consciousness, a new person who is able to see and understand reality, express the fact, express themselves, discover and take responsibility to be an element of change actually. We conclude that the toys games and play because it is movement and body culture, have direct implications for physical education, reducing the possibilities for us to improve the practice of teaching to make use of the rescue of traditional games and activities, while respecting the reality of the environment which we operate, the need for teachers involved and the desired objectivity.
Keywords: Games; toys and games - Physical Education - Teacher Education.